2017
DOI: 10.30638/eemj.2017.133
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Reporting by Oil and Gas Multinationals From Russia and Romania: A Comparative Analysis

Abstract: The objective of the paper consists in determining the level of awareness towards sustainability and ecological issues for Russian and Romanian oil and gas multinational companies (MNCs). Thus, we employed a qualitative approach on the issue, both by investigating the information disclosed in sustainability and/or CSR reports from a sample of Russian and Romanian corporations and by keeping trace of the adequacy of their reporting practice with the Global Reporting Initiative (GRI) standards. Our results subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Naturally, this perception is fully in compliance with the vision of the internal pro-integration EU tandem -the European Commission and the Court of Justice of the EU [19][20][21]. However, other studies are less conclusive about the reconciliation of the EU values with CSR [22], the determination of competitors to go altruistically for the CSR [23], the reports about it and the general endorsement by the community promoting social norms [24]. Some authors even propose that empirical analysis shows such a complexity of the CSR reporting, and its conversion, that both it might be spontaneous as well as regulated and its realization is at the edge of feasibility [25], if not even beyond [26].…”
Section: Introductionmentioning
confidence: 77%
“…Naturally, this perception is fully in compliance with the vision of the internal pro-integration EU tandem -the European Commission and the Court of Justice of the EU [19][20][21]. However, other studies are less conclusive about the reconciliation of the EU values with CSR [22], the determination of competitors to go altruistically for the CSR [23], the reports about it and the general endorsement by the community promoting social norms [24]. Some authors even propose that empirical analysis shows such a complexity of the CSR reporting, and its conversion, that both it might be spontaneous as well as regulated and its realization is at the edge of feasibility [25], if not even beyond [26].…”
Section: Introductionmentioning
confidence: 77%
“…Despite the fact that OHS reporting still represents an under-researched issue in Romanian literature, we can highlight some obvious trends that emerged from our study. First of all, subsidiaries of multinationals (such as OMV Petrom, Arcelor Mittal, Alro and many others) play a dominant role in terms of disseminating good reporting practices from their parent companies [2]. Secondly, since lately the OHS issues are receiving more attention, the specifics of the sector in which a company is operating significantly impose a significant impact on the value of the OHS global reporting index.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mentioned figures give a global overview on the magnitude of the phenomenon of non-financial reporting at national level, for the research we undertake within the present article, it would be more relevant to approximate the total number of Romanian companies that publish non-financial reports after to January 1, 2017, when the effective transposition of Directive 2014/95 / EU into the Romanian legislation took place. Analysing a series of relevant research works emerged in the Romanian literature in relation with the issues of sustainability and CSR (Păun [2]; Lungu et al [41]; Dura et al [42][43][44]; Băleanu et al [45]; Filip et al [46]; Iamandi et al [47]) and taking into account at the same time the content of the reports and studies published by prestigious consultancy firms that have undertaken researches in this domain or in related fields [48][49][50][51], we found that the number of companies that report non-financially in Romania in the period 2017-2018 is much lower than initially expected.…”
Section: The Samplementioning
confidence: 99%